How to Make Higher Education Institutions Innovative: An Application of Market Orientation Practices - Sathana, V.; Jebarajakirthy, C.; Shankar, A. (Routledge Taylor & Francis Group, 2019)
In the present era, higher education is considered a booming and significantly contributing sector to the economy of many coun tries. Due to the intense competition prevailing in the higher education sector, higher education institutions need to become market oriented and innovate in courses, delivery methods and student support services. Consequently, they could meet increas ing expectations placed on them for quality of education and support services. The main aim of this study is to investigate the influence of both market orientation and its dimensions, on innovation in higher education institutions. This study also con sidered the age of the faculty a moderator to these influences. The sample comprised 270 managers and course cordinators attached to faculties, schools or units in Sri Lankan higher educa tion institutions. The surveys were administered for data collec tion. The study has several contributions to the literature- all the three dimensions of market orientation, significantly and posi tively influenced innovation in higher education institutions. The age of the faculty significantly moderated the influence of both market orientation and its dimensions (Intelligence Generation and Responsiveness), on innovation. This study also expand the focus of theory of six sigma by applying it from market orienta tion and customer orientation perspectives. Finally, this study has modified items measuring several constructs to suit the higher education context which canbeusedbyfuture researchers. From the findings, several practical implications are given to officials in higher education institutions for innovating in courses, delivery methods and support services. The article concludes with many useful directions for future researchers.
Keywords: Age of the faculty; Dimensions of market orientation; Higher education institutions; Innovation; Market orientation